2013
DOI: 10.1371/journal.pone.0064623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cagPAI and T4SS on the Inflammatory Response of Human Neutrophils to Helicobacter pylori Infection

Abstract: Helicobacter pylori contains a pathogenicity island, cagPAI, with genes homologous to components of the type IV secretion system (T4SS) of Agrobacterium tumefaciens. The T4SS components assemble a structure that transfers CagA protein and peptidoglycan into host epithelial cells, causing the increased release of interleukin 8 (IL8) from the cells. The Toll-like receptors on neutrophils recognize H. pylori, initiating signaling pathways that enhance the activation of NF-κB. However, the roles of cagPAI and T4SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Results from these studies indicate that zinc homeostasis plays an important role in regulating the cag T4SS in H. pylori . Previous reports have shown that when H. pylori interacts with gastric epithelial cells, the cag T4SS translocates CagA into host cells leading to activation of c-Src and changes in the cytoskeleton [34] [36] . A functional cag T4SS also increases the activation of NOD and NFkB [33] , which ultimately results in the production of IL-8 and the recruitment of neutrophils [34] [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies indicate that zinc homeostasis plays an important role in regulating the cag T4SS in H. pylori . Previous reports have shown that when H. pylori interacts with gastric epithelial cells, the cag T4SS translocates CagA into host cells leading to activation of c-Src and changes in the cytoskeleton [34] [36] . A functional cag T4SS also increases the activation of NOD and NFkB [33] , which ultimately results in the production of IL-8 and the recruitment of neutrophils [34] [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez‐Zauco et al. elegantly demonstrated that the cag PAI and the type IV secretion system (T4SS) have a great impact on the inflammatory response of neutrophils to H. pylori . They observed that H. pylori downregulates neutrophil expression of TLRs 2 and 5 but upregulates TLR9 expression in a cag PAI and T4SS‐independent manner.…”
Section: Innate Immunitymentioning
confidence: 99%
“…H. pylori contains many virulence factors, including the cag pathogenicity island ( cag PAI), that are involved in the pathogenesis of several diseases 1, 23, 4.…”
Section: Introductionmentioning
confidence: 99%